Infarct Size Following Treatment With Second‐ Versus Third‐Generation P2Y12 Antagonists in Patients With Multivessel Coronary Disease at ST‐Segment Elevation Myocardial Infarction in the CvLPRIT Study. Issue 6 (June 2016) - Khan, Jamal N.; Greenwood, John P.; Nazir, Sheraz A.; Lai, Florence Y.; Dalby, Miles; Curzen, Nick; Hetherington, Simon; Kelly, Damian J.; Blackman, Daniel; Peebles, Charles; Wong, Joyce; Flather, Marcus; et al.
Abstract : Background: Third‐generation P2Y12 antagonists (prasugrel and ticagrelor) are recommended in guidelines on ST‐segment elevation myocardial infarction. Mechanisms translating their more potent antiplatelet activity into improved clinical outcomes versus the second‐generation P2Y12 antagonist clopidogrel are unclear. The aim of this post hoc analysis of the Complete Versus Lesion‐Only PRImary PCI Trial‐CMR (CvLPRIT‐CMR) substudy was to assess whether prasugrel and ticagrelor were associated with reduced infarct size compared with clopidogrel in patients undergoing primary percutaneous coronary intervention. Methods and Results: CvLPRIT‐CMR was a multicenter, prospective, randomized, open‐label, blinded end point trial in 203 ST‐segment elevation myocardial infarction patients with multivessel disease undergoing primary percutaneous coronary intervention with either infarct‐related artery–only or complete revascularization. P2Y12 inhibitors were administered according to local guidelines. The primary end point of infarct size on cardiovascular magnetic resonance was not significantly different between the randomized groups. P2Y12 antagonist administration was not randomized. Patients receiving clopidogrel (n=70) compared with those treated with either prasugrel or ticagrelor (n=133) were older (67.8±12 versus 61.5±10 years, P <0.001), more frequently had hypertension (49% versus 29%, P =0.007), and tended to have longer symptom‐to‐revascularization time (234 versus 177 minutes, P =0.05). Infarct size (median 16.1% [quartiles 1–3, 10.5–27.7%] versus 12.1% [quartiles 1–3, 4.8–20.7%] of left ventricular mass, P =0.013) and microvascular obstruction incidence (65.7% versus 48.9%, P =0.022) were significantly greater in patients receiving clopidogrel. Infarct size remained significantly different after adjustment for important covariates using both generalized linear models ( P =0.048) and propensity score matching ( P =0.025). Conclusions: In this analysis of CvLPRIT‐CMR, third‐generation P2Y12 antagonists were associated with smaller infarct size and lower microvascular obstruction incidence versus the second‐generation P2Y12 antagonist clopidogrel for ST‐segment elevation myocardial infarction. Clinical Trial Registration: URL:http://www.isrctn.com/ISRCTN70913605 .